Quantitative analysis and clinical application of iris circulation in ischemic retinal disease - Yanwen Jia (BMC, 2021)
Abstract Background To evaluate quantitative changes in iris blood circulation in patients with ischemic risk. Methods This observational case-control study included 79 patients with diabetic retinopathy (DR) and retinal vein occlusion (RVO). The RVO group included 21 patients; the monocular proliferative diabetic retinopathy (PDR) group included 19 patients; the nondiabetic retinopathy (NDR) group included 18 patients; and the healthy control group included 21 healthy controls. In the RVO group, we analyzed RVO affected eyes, RVO contralateral eyes, and healthy control eyes. We also compared eyes with PDR and contralateral eyes without PDR, patients with diabetes mellitus (DM) without DR, and healthy control eyes. The microvascular networks of the iris and retina were analyzed using optical coherence tomography angiography. The analysis included vessel area density (VAD) and vessel skeleton density (VSD) of iris and retina. Results In the RVO group, the VAD and VSD of iris in the affected eye were higher than those in contralateral and healthy control eyes, and the VAD and VSD of contralateral eyes were higher than those of healthy control eyes. The retinal blood flow of the RVO eyes was less than that of the contralateral and healthy control eyes, but there were no difference between the contralateral eyes and healthy control eyes. The VAD and VSD of iris in PDR were larger than nonproliferative diabetic retinopathy (NPDR) and the NPDR were larger than NDR. There were no differences between NDR and healthy control eyes. Also, there were no differences among the four groups with respect to retinal blood flow. Conclusions Compared with the retina, iris blood circulation quantitative analysis data seem to be more sensitive to ischemia and may be used as a new predictor of ischemic disease, even if further research is needed to better understand the clinical value and importance of this analysis. Trial registration The trial is registered with the clinical trial registration number nct03631108 .